Clearance by microglia depends on packaging of phagosomes into a unique cellular compartment - Villani, Ambra; Benjaminsen, Jørgen; Hartmann, Jonas (Developmental cell, 2019)
Phagocytic immune cells such as microglia can engulf and process pathogens and dying cells with high efficiency while still maintaining their dynamic behavior and morphology. Effective intracellular processing of ingested cells is likely to be crucial for microglial function, but the underlying cellular mechanisms are poorly understood. Using both living fish embryos and mammalian macrophages, we show that processing depends on the shrinkage and packaging of phagosomes into a unique cellular compartment, the gastrosome, with distinct molecular and ultra-structural characteristics. Loss of the transporter Slc37a2 blocks phagosomal shrinkage, resulting in the expansion of the gastrosome and the dramatic bloating of the cell. This, in turn, affects the ability of microglia to phagocytose and migrate toward brain injuries. Thus, this work identifies a conserved crucial step in the phagocytic pathway of immune cells and provides a potential entry point for manipulating their behavior in development and disease.
Gesehen am 03.06.2019